PTH-093 Efficacy of Methotrexate in Ulcerative Colitis: A District General Hospital Experience. (4th June 2013) - Basuroy, R; Johnson, H E; Hollingworth, T; Weaver, S A; McLaughlin, S D
Abstract : Introduction: Uncontrolled studies have reported methotrexate (MTX) to be efficacious in patients with Ulcerative Colitis (UC). British Society of Gastroenterology guidelines recommend MTX in patients who are unresponsive or intolerant of thiopurines. Biologics are not available for UC because of local funding restrictions. Our practise is to only consider MTX in UC patients who have failed thiopurine therapy despite dose optimisation, including allopurinol co-therapy, to achieve therapeutic 6-thioguanine (TGN) and normal methylmercaptopurine nucleotide (MMPN) levels. To the best of our knowledge this is the first study to assess the clinical outcome of UC patients treated with MTX following thiopurine dose optimisation. Methods: Patients with UC treated with MTX were identified from a prospective IBD database. Outcomes following treatment with thiopurines were identified. All patients received MTX with folic acid supplementation. Patients were loaded with intramuscular 25mg MTX for 16 weeks followed by weekly maintenance MTX of 15mg. Clinical response at 16 weeks and 12 months was used to assess the efficacy of MTX. Results: 9 patients (male = 8) with UC treated with MTX were identified. Median age was 47.3 years (range; 24.8–77.8). Median time since diagnosis was 4.5 years (range; 1–25.5). Disease extent was extensive (n = 5), left sided (n = 1) and rectosigmoiditis (n = 3). Thiopurines had previously been discontinued in 9 patients because they were intolerant (n = 5) or unresponsive (n = 4) despite therapeutic TGN and normal MMPN levels. 2 patients (22%) entered a steroid-free clinical remission with MTX at 16 weeks, which was sustained at 12 months. Both were intolerant of thiopurines because of severe nausea and dyspepsia. 7 patients (78%) discontinued MTX at 16 weeks because of a lack of response (n = 6) or side effects (n = 1, pneumonitis). Clinical outcomes at 12 months for patients who failed MXT were colectomy (n = 4), arsenic suppositories (n = 2), and diagnostic reclassification (n = 1) to Crohn's disease with CMV colitis treated with ganciclovir and infliximab. Conclusion: The efficacy of MTX in UC patients in this study was poor with a low clinical response rate (22%) and high colectomy rate (44%). Previous retrospective studies have reported MTX to be efficacious in patients failing thiopurines without reporting on the use of thiopurine optimisation. This study suggests that MTX has limited use in UC patients who are unresponsive to thiopurines despite dose optimisation. Disclosure of Interest: R. Basuroy: None Declared, H. Johnson Conflict with: Sponsorship from Falk, Abbott & Warner Chilcott to attend meetings, T. Hollingworth: None Declared, S. Weaver Consultant for: MSD advisory board, Conflict with: Sponsorship from Falk, Abbott, MSD & Ferring to attend meetings, S. McLaughlin Conflict with: Sponsorship from Falk to attend meetings